2010
DOI: 10.1007/s12647-010-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of accuracy of multi-axis machine tools through error measurement and compensation of errors using laser interferometry technique

Abstract: The present era is witnessing advancement in digital electronics and microprocessor which enables manufacturing sector capable to produce complex components within small tolerance zone in the tune of nanometre and at one machining center. All motion control systems have some form of position feed back system fitted with the machine. Such systems are not generally accurate due to the errors in the positioning performance of the machine tool which will change over time to time due to wear, damage and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In order to study the propagation of various actual errors in the process of solving the spherical center coordinates, and analyze their influence on the final measurement accuracy, the degree of influence of various influencing factors on the measurement performance of the measuring instrument can be calculated through the Guide to the Expression Uncertainty in Measurement(GUM) and Monte Carlo Method(MCM) based on the Eqs. (6). The analysis of the degree of influence of specific hardware precision parameters on measurement accuracy will be given in section 4.2 and the analysis results will be given in section 5.1 for a specific case.…”
Section: The Constraint Model Of Measurement Performance Indexes For the R-testmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to study the propagation of various actual errors in the process of solving the spherical center coordinates, and analyze their influence on the final measurement accuracy, the degree of influence of various influencing factors on the measurement performance of the measuring instrument can be calculated through the Guide to the Expression Uncertainty in Measurement(GUM) and Monte Carlo Method(MCM) based on the Eqs. (6). The analysis of the degree of influence of specific hardware precision parameters on measurement accuracy will be given in section 4.2 and the analysis results will be given in section 5.1 for a specific case.…”
Section: The Constraint Model Of Measurement Performance Indexes For the R-testmentioning
confidence: 99%
“…Assuming that the three sensors have the same indication precision(ΔL1=ΔL2=ΔL3=ΔL), the method of variable parameters is used to analyze and observe the influence of the precision of the sensor's indication and the ball radius on the final measuring accuracy of the measuring instrument based on the Eqs. (6). And the sensitivity coefficient is used to characterize the degree of influence more intuitively.…”
Section: Optimal Configuration Of Hardware Precision Parameters Based On the Measurement Accuracy Constraint Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…chopped fibres and woven roving, and discovered that as the particle strength and specimen hardness increased, so did the impact strength and specimen hardness. Barman et al [11] investigated the impact of the laser interferometry technique and demonstrated that these laser measurement systems provide higher accuracy and quality. Kumar et al found out the during the turning of nanocomposites Al2219 alloy matrix there is a formation of build up edge at lower cutting speed values.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, growing demand for micromachining with minimal capital investment has inspired further studies for investigating the capabilities of different methods and actuators. 1,2 Since pneumatic systems have many distinguishable features such as energy saving, cleanliness, ease of maintenance, accessibility of air, simple structure and operation, and low cost and high power-to-weight ratio, they have been extensively used for many years in industrial automation (Moor 3 ). Since pneumatic actuators are soft and compliant, their application in rehabilitative robots has been studied by a growing number of researchers.…”
Section: Introductionmentioning
confidence: 99%